Correction: Paper-based ELISA diagnosis technology for human brucellosis based on a multiepitope fusion protein. - Dehui Yin; Qiongqiong Bai; Xiling Wu; Han Li; Jihong Shao; Mingjun Sun; Hai Jiang; Jinpeng Zhang (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pntd.0009695.].